Implementasi Manajemen Pendidikan Karakter dalam Mengembangkan Minat dan Sikap Positif Siswa di SMPI Al-Amin Sungai Raya - Muriyeh (UNISAN JURNAL, 2024)
This research aims to explore the implementation of character education management in developing students’ interests and positive attitudes at SMPI Al-Amin Sungai Raya. The research method used is a qualitative approach with a case study as the design. Data was collected through observation, interviews and document analysis. The research results show that SMPI Al-Amin has implemented various character education management strategies, including the formation of a character committee, training for teachers, and integration of character in the curriculum. This implementation has had a positive impact on students’ interest in learning and the formation of positive attitudes towards themselves, the environment and each other. Students show an increase in active participation in school activities, concern for the environment, and awareness of the importance of character values in everyday life. However, challenges such as limited resources and uneven understanding of the concept of character education still need to be overcome. This research contributes to practical understanding of the implementation of character education management in Islamic education environments and provides insight into the development of character education policies in similar institutions. Research supports the need to integrate a character approach in the curriculum as an integral part of students’ holistic education. In conclusion, the management of character education at SMPI Al-Amin Sungai Raya has succeeded in increasing students’ interest in learning and positive attitudes, although there is still room for further improvement in facing existing challenges.